IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM BERDASARKAN KMA NOMOR 165 TAHUN 2014 DI MADRASAH - Mulabbiyah Mulabbiyah (Jurnal Tatsqif, 2018)
The current research intends to clarify (1) the implementation of the two-thousand-and-thirteen curriculum for Islamic Education at Primary Islamic Schools of Mataram, including three aspects of learning, such as planning, teaching, and assessment, and (2) the obstacles in implementing the curriculum. It is a qualitative research utilizing teacher interviews and document studies as the source of the data. The findings indicate that the subjects had implemented the two-thousand-and-thirteen curriculum at the three aspects of learning, such as teaching plan, teaching implementation dan teaching assessment. However, there are some obstacles faced by the subject, such as lack of understanding abbot the two-thousand-and-thirteen curriculum, too many teacher-administration tasks, teaching time-limit, abnormal of student number, difficulties in implementing scientific approach, lack of facilities to support the learning, abnormal number of assessment instruments to be filled, and difficulties in completing online student report.